Effectiveness of the Sports Training Program Monitor on extracurricular activities of high school students in Central Java - Pratama, Rivan Saghita; Nasuka; Rahayu, Setya; Budiono, Irwan; Ramadhan, Indra; Nur Ulinnuha, Rizam Ahada; Santosa, Teguh; Nadzalan, Ali MD (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The Sports Training Program Monitor is an Android-based application that can record the performance of a workout program performed by students. This study aimed to identify the effectiveness of the application of sports training program monitoring on extracurricular activities of high school students in Jawa Tengah province. This study employed a quantitative research design using the survey method. The sampling technique was purposive sampling, and the research instrument was a questionnaire. The total sample consisted of 128 students (41 male and 87 female). Their mean body weight was 43.76±5.89 kg, height 1.62±0.09 m, and BMI 16.92±3.15 kg/m². The average duration of exercise was 2.03 ± 0.50 weeks. The effectiveness percentage of the application was 95.66% based on 128 samples, indicating that the application has a very high efficiency score. The implementation of sports training program monitoring has a very high level of effectiveness in monitoring student activities in managing extracurricular training. Teachers and students are encouraged to use this application to manage extracurricular sports programs, as it can help develop students’ athletic potential and maintain accurate training records for extracurricular activities.